A comparative study to evaluate the postoperative results between tympanoplasty alone and tympanoplasty with cortical mastoidectomy in chronic suppurative otitis media - Naik, Kiran; K. S., Ravi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic suppurative otitis media (CSOM) is a common ear disease presenting to the ENT OPD. It’s the most common cause of hearing dysfunction in our country. Most of these cases requires surgery but still controversial. In the surgical management of CSOM even well experienced otologist have the dilemma whether to combine mastoidectomy with tympanoplasty or not. Objectives of the study was to study and evaluate whether the additional mastoidectomy procedure helps in the outcome in the surgical treatment of CSOM in terms of graft uptake, perforation closure, improvement in hearing, disease eradication and recurrence. Methods: The 40 patients of age group 12 to 65 years diagnosed with CSOM of tubotympanic type in inactive or quiescent stage was taken as study group. Tympanoplasty alone was done in 20 cases and tympanoplasty with cortical mastoidectomy was done in 20 cases. Hearing gain following surgery and factors influencing the outcome were measured. Study done was prospective comparative study. Results: Graft uptake was seen in 17 cases (85%) in tympanoplasty alone group and 15 cases (75%) in Tymapanomastoidectomy group at the end of 2nd month. Graft uptake was found to be same in terms of significance in both groups. Post-operative hearing gain was observed in 75% of patients in each group Conclusions: Hearing improvement, graft uptake were statistically incomparable in two groups. Combining cortical mastoidectomy with tympanoplasty will not give additional benefits in terms of hearing gain, graft uptake and disease eradication if the middle ear mucosa is healthy.